The Archetypal Symbols and The Hero’s Journey of Alice in Wonderland Film - Rohmatul Fitriyah Dewi; Darini Yusrina A (Faculty of Language and Literature, University of Surakarta, 2023)
Myth is a classic story about heroes who explain the origins of natural occurrences. Myth is not always given historically since the modern one will continue to evolve and impact cinema creation. This study aimed to look at the categorization of Campbell's